Growth without economic transformation: Economic impacts of Ghana's political settlement - Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2011)
Since the Fourth Republic was inaugurated in 1993, politics in Ghana has been increasingly characterized by competitive clientelism. Ruling coalitions are characterized by a high degree of vulnerability in power due to a strong opposition party, by strong lower-level factions within the ruling coalition due to their importance in winning elections, and by a high degree of fragmentation among the ruling elite. These characteristics, combined with a weak domestic capitalist class and high inflows of foreign aid, have led the ruling elites across political parties to pursue and implement policies that have a short time horizon, that do not significantly shift the allocation of resources towards building productive sectors, and which are often plagued by problems of enforcement. The results have led to growth without economic transformation. In particular, the country has witnessed recurrent macroeconomic instability, a haphazard process of privatization of state-owned enterprises, and no serious attempt to build up productive sectors outside of cocoa and gold.
Keywords: 330; Wachstumspolitik; Wirtschaftsförderung; Wirtschaftsreform; Patronage; Ghana